Protection of Indonesian Migrant Workers: Strategies for Sustainable Policies and Best Practices - Al Farisi, Salman; Darwin, Muhadjir; Mas'oed, Mochtar; Sukamdi, Sukamdi (Political Science Program, Universitas Negeri Semarang, 2022)
Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers is a policy product that is a comprehensive correction to Law Number 39 of 2004 on the Placement and Protection of Indonesian Migrant Workers. Law Number 18/2017 mandates stages of protection by the state, from when the Indonesian migrant workers (IMW) candidate has not yet been dispatched; when IMW works in the destination country; and after IMW completes its work contract. The law also regulates the division of tasks among government officials, from the village level; regional government; to the central government, including the network of Representatives of the Republic of Indonesia abroad. The stages of protection services and the involvement of various government agencies and other parties are necessary because the problems surrounding them are also complex. The question that arises is how the policies and actions of these various agencies may interact harmoniously so that IMW protection services can take place on a sustainable basis? This study found that the integration of data and information systems can improve the performance of IMW protection services. The integration of the system also supports the formation of a sustainable IMW protection service ecosystem.